International Partnerships to Develop Evidence-informed Priority Setting Institutions: Ten Years of Experience from the International Decision Support Initiative (iDSI) - Peter Baker; Edwine Barasa; Kalipso Chalkidou; Lumbwe Chola; Anthony Culyer; Saudamini Dabak; Victoria Y. Fan; Katrine Frønsdal; Lieke Fleur Heupink; Wanrudee Isaranuwatchai; Rahab Mbau; Abha Mehndiratta; et al. (Taylor & Francis Group, 2023)
All health systems must set priorities. Evidence-informed priority-setting (EIPS) is a specific form of systematic priority-setting which involves explicit consideration of evidence to determine the healthcare interventions to be provided. The international Decision Support Initiative (iDSI) was established in 2013 as a collaborative platform to catalyze faster progress on EIPS, particularly in low- and middle-income countries. This article summarizes the successes, challenges, and lessons learned from ten years of iDSI partnering with countries to develop EIPS institutions and processes. This is a thematic documentary analysis, structured by iDSI's theory of change, extracting successes, challenges, and lessons from three external evaluations and 19 internal reports to funders. We identified three phases of iDSI's work-inception (2013-15), scale-up (2016-2019), and focus on Africa (2019-2023). iDSI has established a global platform for coordinating EIPS, advanced the field, and supported regional networks in Asia and Africa. It has facilitated progress in securing high-level commitment to EIPS, strengthened EIPS institutions, and developed capacity for health technology assessments. This has resulted in improved decisions on service provision, procurement, and clinical care. Major lessons learned include the importance of sustained political will to develop EIPS; a clear EIPS mandate; inclusive governance structures appropriate to health financing context; politically sensitive and country-led support to EIPS, taking advantage of policy windows for EIPS reforms; regional networks for peer support and long-term sustainability; utilization of context appropriate methods such as adaptive HTA; and crucially, donor-funded global health initiatives supporting and integrating with national EIPS systems, not undermining them.